KAIDAH PENYUSUNAN TES BAHASA ARAB (PILIHAN GANDA): PREPARATION RULES OF ARABIC TEST (MULTIPLE CHOICE TEST) - Erlina (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2022)
This study aims to explain how the rules for preparing the Arabic test in the form of multiple choice tests must be understood and applied by all parties involved in the preparation of the multiple choice Arabic test. This study uses a qualitative descriptive research method that is used to investigate, find, describe and explain a phenomenon. The results of the study show that there are three aspects of the rules for preparing multiple choice Arabic tests, namely material, construction and language aspects. Material rules; the subject matter must be in accordance with the indicators and competencies, must be homogeneous and logical, each question has only one answer. Construction rules; the subject matter is formulated briefly and clearly, the questions and answers contain only the necessary statements, do not provide clues towards the correct answer, do not contain double negative statements, the length of the formulation of the answer choices must be relatively the same, the answer choices may not contain the statement